145k views
1 vote
Please... help me..I have a confusion..

is the (-5 + -3 ) is =( -5 - +3)​

1 Answer

2 votes

Answer:

They are the same

Explanation:

We are to check if (-5 + -3 ) =( -5 - +3)​

First you must know that the product of a positive and a negative n=sign will result in a negative sign i.e. + * - = -

Applying this in question;

(-5 + -3 )

= -5 - 3

= -8

similarly

( -5 - +3)​

= -5 - 3

= -8

Since both values are the same hence, (-5 + -3 ) =( -5 - +3)

User Beefeather
by
6.1k points